Analysis of Family Nursing Problems: Inability of Family Coping in Tuberculosis Families with Diabetes Mellitus - Firdausiah, Laylatul; Susanto, Tantut; Ati, Niken Asih Laras; Bahtiar, Syahroni (Al-Hijrah Indonesia, 2024)
Tuberculosis (TB) and Diabetes Mellitus (DM) are two health problems that are quite large epidemiologically and have a major impact globally because they are both chronic and interrelated diseases. Diabetes Mellitus health problems with tuberculosis can change coping in the family, the family will provide adaptive behaviors such as supporting sick family members or maladaptive such as limiting himself to adapt to family health problems. The purpose of this study is to analyze family nursing problems: family coping disabilities in Tuberculosis with Diabetes Mellitus families in the working area of the Ajung Health Center. The participants in this study were two families in the working area of the Ajung Health Center, Jember Regency, namely Mr. L's family and Mrs. N's family. This study was conducted through family nursing care coaching for 3 weeks, assisted families were given family nursing care with 6 times visits for 30 minutes. This case study method emphasizes the analysis of nursing problems from family coping disabilities in Tuberculosis with Diabetes Mellitus families in depth, meaning researchers who want to examine a single event. The results of the case study showed that both families had nursing problems, family coping disabilities. As a nurse, it is very important to recognize the emotional and psychological difficulties experienced by adapting families and learn how to coping with family coping disabilities. Providing emotional support is part of a nurse's job, understanding the nursing diagnosis in this case is key.